The Role Of Soil In Agriculture Of The Republic Of Karakalpakstan And Soil Conservation Measures (Eurasian Journal of Learning and Academic Teaching, 2026)
This study examines the role of soil in the agriculture of the Republic of Karakalpakstan and analyzes soil conservation measures aimed at improving land productivity and environmental sustainability. Particular attention is given to soil degradation processes such as salinization, erosion, and desertification, which significantly affect agricultural efficiency in the region. The research highlights the importance of sustainable soil management practices, including irrigation regulation, crop rotation, organic fertilization, and land reclamation techniques.